Dynamics of Prochlorococcus Diversity and Photoacclimation During Short-Term Shifts in Water Column Stratification at Station ALOHA - Thompson, Anne W.; van den Engh, Ger; Ahlgren, Nathan A.; Kouba, Kathleen; Ward, Samantha; Wilson, Samuel T.; Karl, David M. (Frontiers in Marine Science, 2018)
The cyanobacterium Prochlorococcus is the dominant phototroph in surface waters of the vast oligotrophic oceans, the foundation of marine food webs, and an important component of global biogeochemical cycles. The prominence of Prochlorococcus across the environmental gradients of the open ocean is attributed to its extensive genetic diversity and flexible chlorophyll physiology, enabling light capture over a wide range of intensities. What remains unknown is the balance between temporal dynamics of genetic diversity and chlorophyll physiology in the ability of Prochlorococcus to respond to a variety of short (approximately one day) and longer (months to year) changes in the environment. Previous field research established depth-dependent Prochlorococcus single cell chlorophyll distributions in the North Pacific Subtropical Gyre. Here, we examined whether the shifts in chlorophyll distributions correspond to changes in Prochlorococcus genetic diversity (i.e. ecotype-level community structure) or photoacclimation of stable communities over short time intervals. We report that community structure was relatively stable despite abrupt shifts in Prochlorococcus chlorophyll physiology, due to unexpected physiological plasticity of high-light adapted Prochlorococcus ecotypes. Through comparison with seasonal-scale changes, our data suggest that variability on daily scales triggers shifts in Prochlorococcus photoacclimation, while seasonal-scale dynamics trigger shifts in community structure. Together, these data highlight the importance of incorporating the process of photoacclimation and chlorophyll dynamics into interpretations of phytoplankton population dynamics from chlorophyll data as well as the importance of daily-scale variability to Prochlorococcus ecology.